Energy and Sustainability IV 2013
DOI: 10.2495/esus130201
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance strategies and local impact of MSW incinerators

Abstract: The present paper gives a contribution to the understanding of the effects of variations in maintenance scheduling on the environmental impact of municipal solid waste incinerators. The proposed approach allows a vision of their impact beyond the conventional balances. The characteristics of a selected case study were put forward and discussed. A plant proposed for a region in the North East of Italy was chosen for the scheduling effects analysis because of the long period of non-operation of each waste treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The AD and composting parameters are in agreement with [21] and incinerator indicators with a real facility in Milan [24]. No data were found for NH 3 and CH 4 , N 2 O respectively, for the anaerobic/aerobic and combustion process.…”
Section: Environmental Assessmentsupporting
confidence: 80%
See 1 more Smart Citation
“…The AD and composting parameters are in agreement with [21] and incinerator indicators with a real facility in Milan [24]. No data were found for NH 3 and CH 4 , N 2 O respectively, for the anaerobic/aerobic and combustion process.…”
Section: Environmental Assessmentsupporting
confidence: 80%
“…Today, the most mature and robust technology for energy recovery is incineration, where in Europe more than 20% of the MSW stream is valorised [2,3]. The main advantages of Solid Recovered Fuel (SRF) incineration over using MSW as fuel can be summed up in higher process efficiency, better quality of flue gases and significant reduction of heavy metals in the fly ashes.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment the linear economy is being gradually replaced by the CE that aims towards a zero waste framework [12][13][14][15][16] The main factors that are underlying the bases of any sustainable waste management are the reliable and up-to-date information and their trends regarding the quantitative and qualitative characteristics of the MSW stream, considering the demographic changes, the socio-economic and technological maturity, environmental policies, decision-makers and the interests of the parties involved in the process [17][18][19]. The most advanced and sustainable, Integrated Municipal Solid Waste Management Systems must maintain an equilibrium between the separately collected (SC) waste fractions and the Residual Municipal Solid Waste (RMSW), both of them being suitable for material and energy recovery.…”
Section: Role Of Energy Recovery From Msw In a Frame Of Materials Recomentioning
confidence: 99%
“…Several studies have demonstrated the increased interest in waste management, environmental legislation and recently, from a public viewpoint [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%